The M(1) muscarinic acetylcholine receptor subtype is important for retinal neuron survival in aging mice - Laspas, Panagiotis (Sci Rep, 2019)
Muscarinic acetylcholine receptors have been implicated as potential neuroprotective targets for glaucoma. We tested the hypothesis that the lack of a single muscarinic receptor subtype leads to age-dependent neuron reduction in the retinal ganglion cell layer. Mice with targeted disruption of single muscarinic acetylcholine receptor subtype genes (M(1) to M(5)) and wild-type controls were examined at two age categories, 5 and 15 months, respectively. We found no differences in intraocular pressure between individual mouse groups. Remarkably, in 15-month-old mice devoid of the M(1) receptor, neuron number in the retinal ganglion cell layer and axon number in the optic nerve were markedly reduced. Moreover, mRNA expression for the prooxidative enzyme, NOX2, was increased, while mRNA expression for the antioxidative enzymes, SOD1, GPx1 and HO-1, was reduced in aged M(1) receptor-deficient mice compared to age-matched wild-type mice. In line with these findings, the reactive oxygen species level was also elevated in the retinal ganglion cell layer of aged M(1) receptor-deficient mice. In conclusion, M(1) receptor deficiency results in retinal ganglion cell loss in aged mice via involvement of oxidative stress. Based on these findings, activation of M(1) receptor signaling may become therapeutically useful to promote retinal ganglion cell survival.